2020
DOI: 10.1126/sciadv.aaz7809
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics identifies multiple pathways underlying antitumor function of TCR- and CD8αβ-engineered human CD4 + T cells

Abstract: Transgenic coexpression of a class I–restricted tumor antigen–specific T cell receptor (TCR) and CD8αβ (TCR8) redirects antigen specificity of CD4+ T cells. Reinforcement of biophysical properties and early TCR signaling explain how redirected CD4+ T cells recognize target cells, but the transcriptional basis for their acquired antitumor function remains elusive. We, therefore, interrogated redirected human CD4+ and CD8+ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 60 publications
4
35
0
Order By: Relevance
“… 13 Transfer of CD8αβ can redirect CD4+ T cells to class I-restricted antigens, and the transgenic CD4+ T cells become cytotoxic hybrid cells. 14 22–27 We have recently analyzed the transcriptional consequences of TCR8 expression in polyclonal CD4+ and CD8+ T cells by single cell RNA sequencing and experimental validation and showed that transgenic TCR8 has multiple advantages in both CD4+ and CD8+ lineages, promoting an overall enhanced anti-tumor function. 14 We now investigated the impact of transgenic CD8αβ on endogenous class I-restricted TCR function in CD8+ T cells as we hypothesized that combining CD8αβ co-receptor as a transgene with a tumor-targeted TCR is one potential means of overcoming the limitation of reduced anti-viral activity in TCR+ VSTs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 13 Transfer of CD8αβ can redirect CD4+ T cells to class I-restricted antigens, and the transgenic CD4+ T cells become cytotoxic hybrid cells. 14 22–27 We have recently analyzed the transcriptional consequences of TCR8 expression in polyclonal CD4+ and CD8+ T cells by single cell RNA sequencing and experimental validation and showed that transgenic TCR8 has multiple advantages in both CD4+ and CD8+ lineages, promoting an overall enhanced anti-tumor function. 14 We now investigated the impact of transgenic CD8αβ on endogenous class I-restricted TCR function in CD8+ T cells as we hypothesized that combining CD8αβ co-receptor as a transgene with a tumor-targeted TCR is one potential means of overcoming the limitation of reduced anti-viral activity in TCR+ VSTs.…”
Section: Discussionmentioning
confidence: 99%
“… 2–4 6 Several features of the CD8αβ co-receptor most likely explain our findings, including its role in TCR-pMHC recognition and modulation of antigen-sensitivity, 28 recruitment of Lck to the immune synapse, and activation of signaling components that are crucial during early T-cell activation, 29 and, as recently demonstrated by single cell RNA sequencing, its impact on a variety of transcriptional pathways upon tumor challenge that support enhanced anti-tumor function. 14 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations